2013
DOI: 10.1152/ajpregu.00582.2012
|View full text |Cite
|
Sign up to set email alerts
|

Preference for linoleic acid in obesity-prone and obesity-resistant rats is attenuated by the reduction of CD36 on the tongue

Abstract: Chen CS, Bench EM, Allerton TD, Schreiber AL, Arceneaux KP 3rd, Primeaux SD. Preference for linoleic acid in obesity-prone and obesityresistant rats is attenuated by the reduction of CD36 on the tongue. Am J Physiol Regul Integr Comp Physiol 305: R1346-R1355, 2013. First published October 23, 2013 doi:10.1152/ajpregu.00582.2012.-Differential sensing of dietary fat and fatty acids by the oral cavity is proposed to regulate the susceptibility to obesity. In the current experiments, animals that differ in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…This preference response was also reproduced when CD36-null mice were subjected to brief-access licking tests, suggesting that lingual CD36 can play a significant role in this phenomenon (122). The fact that a specific depletion of CD36 in CVP with CD36 siRNA attenuates the preference for LA in rats is consistent with this interpretation (29). Nevertheless, whether naive CD36 Ϫ/Ϫ mice failed to detect properly fat sources during two bottle preference tests, oil-experienced animals displayed near similar attraction for oil emulsion than wild-type controls (187).…”
Section: Cd36supporting
confidence: 58%
“…This preference response was also reproduced when CD36-null mice were subjected to brief-access licking tests, suggesting that lingual CD36 can play a significant role in this phenomenon (122). The fact that a specific depletion of CD36 in CVP with CD36 siRNA attenuates the preference for LA in rats is consistent with this interpretation (29). Nevertheless, whether naive CD36 Ϫ/Ϫ mice failed to detect properly fat sources during two bottle preference tests, oil-experienced animals displayed near similar attraction for oil emulsion than wild-type controls (187).…”
Section: Cd36supporting
confidence: 58%
“…Additionally, in this study FAT/CD36 knock-out obese mice consumed less of an LA solution than their wild type controls [68]. In humans this has been found to result from the rs1761667-AA allele which decreases FAT/CD36 expression, with those who are unable to orally sense LA having a higher fat intake and total EI than those who can [69].…”
Section: Linoleic Acid's Obesogenic Propertiesmentioning
confidence: 61%
“…In contrast to these results, when the same LA EI was combined into an isoenergetic high protein diet, there was insignificant weight gain, with the differences found to be dependent on cyclic adenosine monophosphate (cAMP) activation [67]. Oral sensing may also play a role in LA induced adipogenesis, with obese mice having been shown to have a preference for higher concentrations of oral LA, found to occur due to increased lingual expression of FAT/CD36 (fatty acid translocase cluster of differentiation 36), which has been shown to have a role in fat sensing and tolerance [68].…”
Section: Linoleic Acid's Obesogenic Propertiesmentioning
confidence: 99%
“…Taste receptors that are present on the tongue, do allow for the perception of taste and the importance of the oral cavity in the detection of highly palatable foods has led to a number of studies demonstrating the importance of sweet taste receptors and fatty acid receptors on the tongue. Lingual taste receptors modulate the preference for palatable foods and are regulated by the consumption of palatable foods [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. Our laboratory has demonstrated that consumption of a high fat diet increases lingual and duodenal expression of the fatty acid receptor, CD36, in obesity-prone rats [102].…”
Section: Taste Perception and Food Preferences Following Bariatric Sumentioning
confidence: 99%
“…The detection of tastants by lingual taste receptors leads to the induction of signaling cascades which activate gustatory nerves to transmit sensory information to brain regions associated with the regulation of gustatory information, food intake and reward [107][108][109][110]. Obese animal models and human patients with T2D demonstrate alterations in fat and sucrose preferences and patients with T2D crave higher carbohydrate (sweet taste) foods, which is associated with poor glycemic control [81,94,103,111,112].…”
Section: Taste Perception and Food Preferences Following Bariatric Sumentioning
confidence: 99%